On tyranny and the global legal order - O'Donoghue, Aoife 1981- (Global law series, 2021)
Since classical antiquity debates about tyranny, tyrannicide and preventing tyranny's re-emergence have permeated governance discourse. Yet within the literature on the global legal order, tyranny is missing. This book creates a taxonomy of tyranny and poses the question: could the global legal order be tyrannical? This taxonomy examines the benefits attached to tyrannical governance for the tyrant, considers how illegitimacy and fear establish tyranny, asks how rule by law, silence and beneficence aid in governing a tyranny. It outlines the modalities of tyranny: scale, imperialism, gender, and bureaucracy. Where it is determined that a tyranny exists, the book examines the extent of the right and duty to effect tyrannicide. As the global legal order gathers ever more power to itself, it becomes imperative to ask whether tyranny lurks at the global scale